Peran Strategic Entrepreneurship dalam Memediasi Pengaruh Strategic Agility dan Resource Bricolage terhadap Business Performance pada Industri Hotel di Wilayah Kepulauan: Peran Strategic Entrepreneurship dalam Memediasi Pengaruh Strategic Agility dan Resource Bricolage terhadap Business Performance pada Industri Hotel di Wilayah Kepulauan - Indah Noviyanti; Ryand Daddy Setiawan (JURNAL ILMIAH EDUNOMIKA, 2026)
The non-star hotel industry in island regions faces significant challenges due to dynamic business environments, increasing competition, and limited resources. These conditions require business actors to possess strategic adaptability and creativity in utilizing resources to sustain business performance. This study aims to analyze the effects of strategic agility and resource bricolage on business performance, with strategic entrepreneurship serving as a mediating variable in non-star hotels in the Bangka Belitung Islands Province. This research employs a quantitative approach with an explanatory research design. The research population consists of non-star hotels, with respondents at the managerial, owner, or senior staff levels. The sample was determined using the Slovin formula, while data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that strategic agility has a positive and significant effect on business performance as well as on strategic entrepreneurship. Resource bricolage does not have a significant direct effect on business performance but has a positive and significant effect on strategic entrepreneurship. Furthermore, strategic entrepreneurship has a positive and significant effect on business performance. Mediation analysis shows that strategic entrepreneurship partially mediates the relationship between strategic agility and business performance. These findings suggest that improving the business performance of non-star hotels depends not only on adaptive capabilities and creative resource utilization but also on the organization’s ability to translate these capabilities into strategic entrepreneurial practices.